Changes in Renal Function and Oxidative Status Associated with the Hypotensive Effects of Oleanolic Acid and Related Synthetic Derivatives in Experimental Animals - Madlala, Hlengiwe Pretty; Van Heerden, Fanie Retief; Mubagwa, Kanigula; Musabayane, Cephas Tagumirwa (PLOS ONE, 2015)
Purpose The triterpene oleanolic acid (OA) is known to possess antihypertensive actions. In the present study we to compared the effects of the triterpene on mean arterial blood pressure (MAP) and kidney function following acute administration in normotensive animals with those of its related oleanane synthetic derivatives (brominated oleanolic acid, Br-OA and oleanolic acid methyl ester, Me-OA). We also used experimental models of hypertension to further explore the effects of sub-chronic oral OA treatment and evaluated influences on oxidative status. Methods OA was extracted from dried flower buds of Syzygium aromaticum using a previously validated protocol in our laboratory. Me-OA and Br-OA were synthesized according to a method described. Rats were supplemented with lithium chloride (12 mmol L-1) prior to experimentation in order to raise plasma lithium to allow measurements of lithium clearance and fractional excretion (FELi) as indices of proximal tubular Na+ handling. Anaesthetized animals were continuously infused via the right jugular with 0.077M NaCl. MAP was measured via a cannula inserted in the carotid artery, and urine was collected through a cannula inserted in the bladder. After a 3.5 h equilibration, MAP, urine flow, electrolyte excretion rates were determined for 4 h of 1 h control, 1.5 h treatment and 1.5 h recovery periods. OA, Me-OA and Br-OA were added to the infusate during the treatment period. We evaluated sub-chronic effects on MAP and kidney function in normotensive Wistar rats and in two animal models of hypertension, spontaneously hypertensive rats (SHR) and Dahl salt-sensitive (DSS) rats, during 9-week administration of OA (p.o.). Tissue oxidative status was examined in these animals at the end of the study. Increasing evidence suggests that and renal function disturbances and oxidative stress play major roles in the pathogenesis of hypertension. Results Acute infusion OA and oleanane derivatives displayed qualitatively similar effects in decreasing MAP and increasing urinary Na+ outputs. The drugs increased the FENa and FELi without influencing GFR indicating that at least part of the overall natriuretic effect involved proximal tubular Na+ reabsorption. Sub-chronic OA administration (p.o.) also elicited hypotensive responses in Wistar, DSS and SHR rats. The MAP lowering effect was more marked in hypertensive animals and were positively correlated with increased urinary Na+ excretion. Compared with respective control rats, OA treatment reduced malondialdehyde (MDA, a marker of lipid peroxidation) and increased activities of antioxidant enzymes; superoxide dismutase and glutathione peroxidase in hepatic, cardiac and renal tissues. Conclusions OA and oleanane derivatives have similar effects on MAP, kidney function and oxidative stress. The amelioration of oxidative stress and blood pressure lowering effects by OA are more marked in hypertensive animals and correlated with an increased urinary Na+ output. Novelty of the Work The results of this study are novel in that they show 1) a correlation between blood pressure reduction and increased urinary Na+ excretion by OA, 2) a more marked MAP reduction in hypertensive animals and 3) a drug-induced decrease in proximal tubule Na+ reabsorption. The results may also be clinically relevant because OA is effective via oral administration.